A comprehensive review of remote sensing techniques for monitoring Ulva prolifera green tides - Geng, Xiaomeng; Li, Huiru; Wang, Le; Sun, Weidong; Li, Yize (Frontiers in Marine Science, 2025)
In recent years, Ulva prolifera green tide, as a large-scale marine ecological phenomenon, has occurred frequently in coastal areas such as the Yellow Sea and the East China Sea, significantly affecting marine ecosystems and fishery resources. With the continuous advancement of remote sensing technologies, these technologies have become indispensable tools for monitoring Ulva prolifera green tides. This review provides a comprehensive overview of the advances in remote sensing band indices for detecting green tides, including spatiotemporal distribution analysis, area and biomass estimation, drift trajectory modeling, and investigations of their driving mechanisms. Additionally, it identifies the limitations and unresolved challenges in current approaches, such as constraints on data resolution, algorithmic biases, and environmental variability. The potential for integrating multi-source remote sensing data with marine environmental parameters and deep learning techniques is discussed, emphasizing their roles in improving the accuracy and reliability of monitoring and predicting Ulva prolifera green tides. This review aims to guide future research efforts and technological innovations in this field.